Studies on different genotypes of Indian bathua (Chenopodium album) for thier yield, quality and antioxidant activities - YADAV, R K; JOSHI, SOBUDH; KUMAR, RAJ; KALIA, PRITAM; VERSHNEY, RICHA; JAIN, VARSHA (The Indian Journal of Agricultural Sciences, 2013)
Sixteen genotypes of Chenopodium (Chenopodium album) were evaluated for desired horticultural traits, viz. plantheight (cm), leaf colour, leaf length and width, days to bolting, dry matter (%) and yield/plant (g); and their importantquality traits, total carotene, ascorbic acid, total phenolic content, Cuprac ion Reducing Antioxidant Capacity (CUPRAC)and Ferric Reducing Antioxidant Power (FRAP) were also estimated during rabi/winter season of 2010 and 2011 atDivision of Vegetable Science, IARI, New Delhi. Among the genotypes plant height ranged from 54.7 cm (Desi bathua)to 223 cm (Bathua 2). Yield/plant was recorded maximum in Bathua 13 (280 g) followed by Bathua 12 (277 g). LocalBathua (Desi type) recorded lowest yield 45.1 g/plant; however, it recorded maximum and significantly high dry mattercontent (16.5 %). Considerable variability was recorded in total carotenoids which ranged from 30.7 mg /100g (Bathua 7)to 89.2 mg /100 g (Bathua 10). Bathua 10 also recorded maximum value of ascorbic acid (157.8 mg /100g) which wassignificantly higher than other genotype. High variability was recorded in total phenolic content, which ranged from276.87 Î¼g gallic acid equivalent (GAE)/g (Bathua 6) to 893.83 Î¼g GAE/g (Bathua 13). Antioxidant activities recorded byboth CUPRAC and FRAP method was found high in Bathua 13, Bathua 12 and Desi Bathua. On overall basis, it wasconcluded that Bathua 13, Bathua 12 and Bathua 14 could be the desirable genotypes for increasing yield and quality ofChenopodium. However, Bathua 10 was found rich source of carotene and ascorbic acid and Desi Bathua for high antioxidantactivity. These genotypes can be further utilized to develop nutritionally rich leafy vegetables.